Detailed analysis of skull morphology and brain size in crested Padovana chicken (Gallus gallus f.d.) - Wolf-Vollenbröker, Michael; Petow, Stefanie; Schmidbauer, Max; Fellmin, Mareike; Ulrich, Reiner; Mehlhorn, Julia (Frontiers in Ecology and Evolution, 2024)
Introduction Crested chickens show abnormalities in their anatomy of the skull, endocranium, and brain (including cerebral elongation) and can be appropriate model systems for neuroanatomical evolution, brain–skull integration, and skull and brain deformities. Here, we give a detailed comprehensive description of the skull of crested chickens using the example of the Padovana chicken, including ontogenetic aspects and an allometric analysis of their brain size. Methods In total, 109 chickens of two different strains of the Padovana chicken were hatched together. All animals were X-rayed weekly during growth. Nine juvenile (ready for hatch) and 22 adult skulls were processed for histology and morphological descriptions, and a further 20 individuals were processed for brain analysis. Results At hatching, all chicks were already crested, and a distinctive bony protuberance was first observed at the age of 4 weeks. Juvenile chickens exhibit either an open neurocranium or a protuberance. In the adult skull, foramina of different sizes can be found in the frontal bone, but no completely open neurocrania are observed in juveniles. Particularly in Padovana with cranial protuberances, several peculiarities can be observed in the os mesethmoidale, os nasale, os praemaxillare, orbit, and cranial fossae. Additionally, the brain of Padovana with cranial protuberances looks drawn in length with the shape of an hourglass and showed significantly larger encephalization indices than plain-headed breeds, topped only by another crested chicken breed. Discussion Investigations on chickens with cerebral elongation may facilitate the understanding of skull and brain dysplasia and may provide meaningful insights into cerebral hernia development. Additionally, crested breeds, combined with standard chickens, form a promising comparative system for investigating the emergence of novel brain and skull morphologies.